Preparation of fine MgTa2O6 and Mg4Ta2O9 powders by chemical methods - Navale, SC; Ravi, V (Materials Science and Engineering B-Solid State Materials for Advanced Technology, 2005)
Two different chemical methods are applied to prepare MgTa2O6 (MT2) and Mg4Ta2O9 (M4T2) powders. A gel was formed when a aqueous solution of Mg(NO3)(2), TAF(5) and citric acid in stoichiometric ratio is heated on a water bath. This gel on decomposition at 750 degrees C produced the fine crystallites of ternary oxide, M4T2. A simple co-precipitation technique had been successfully applied for the preparation of pure ultrafine single phase MT2. Ammonium hydroxide was used to precipitate Mg2+ and Ta5+ cations as hydroxides simultaneously. This precursor on heating at 750 degrees produces MT2 powders. The phase contents and lattice parameters were studied by the powder X-ray diffraction (XRD). Particle size and morphology was studied by transmission electron microscopy (TEM). (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Electron microscopy; powders-chemical preparation; X-ray methods